2022
DOI: 10.1007/s13204-022-02714-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pulping routes of rice straw on cellulose nanoarchitectonics and their behavior toward Indigo dye

Abstract: This work deals with emphasizing the relation between particle dimension distribution of nanocellulose (PDD) particles with its efficiency as stabilizing/adsorbent agent of Indigo dye. In this respect, different pulping reagents were used in preparation of Rice straw pulps as precursors for nanocelluloses using acid hydrolysis and oxidizing agents [(KMnO4 and NH4)2S2O8] methods. The PDD was estimated by indirect method through processing the TEM images using the software ImageJ. The resulting nanocelluloses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…According to literature, rice straw may be used efficiently for composite preparation [105][106][107][108][109][110][111]. Furthermore, rice straw microfibrils at 5% increase the characteristics of rice straw polypropylene composites [107].…”
Section: Composition Of Rice Huskmentioning
confidence: 99%
“…According to literature, rice straw may be used efficiently for composite preparation [105][106][107][108][109][110][111]. Furthermore, rice straw microfibrils at 5% increase the characteristics of rice straw polypropylene composites [107].…”
Section: Composition Of Rice Huskmentioning
confidence: 99%
“…Still, lower yields of 61.18 % and 62.40 % were recorded for the same plant material when sodium hydroxide and ethanol were used as the pulping chemicals (Figure 1b). The addition of anthraquinone to sodium hydroxide during pulping has been documented to have increased the yield, improved the chemo-mechanical properties of the products, quickened delignification, prevented redeposition of removed noncellulosic materials and prevented carbohydrate peeling effect [2,7,8]. This study has demonstrated that combining ethanol and anthraquinone can improve pulp yield.…”
Section: Pulp Yieldmentioning
confidence: 69%
“…Material thermal firmness was observed using a thermogravimetric analyzer. Using the absorbance peak height of the FTIR spectra, HBI, LOI, and TCI were calculated using equations ( 6), (7), and (8), respectively.…”
Section: Instrumental Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several challenges can hinder its effective utilization like high silica content, which can make it less palatable and digestible for livestock. Basta et al [9] studied the effects of rice straw pulping processes on cellulose nanoarchitecture and how they react to indigo dye. Low energy content which limits its use as a feedstock for bioenergy production and Slow decomposition.…”
Section: Introductionmentioning
confidence: 99%